Simulation of the supersonic jet length for KT oxygen lance with 22 mm diameter and 2:1 ratio of NG: O2 at electric arc furnace - Mohd Adam, Mohd Noor (2008)
In the last five years the amount of oxygen used into the Electric Arc Furnace (EAF) has increased a lot. This fact is depends on the high cost of the electrical energy, but in general the increment can also be explained with the development of new injection technologies, which have increased the efficiency on the thermal and chemical input into the EAF. In addition to that, the multipoint injection of supersonic oxygen and powder carbon around the EAF, has also given the possibility to automate the melting and refining operations, so that nowadays the furnace operator can perform only supervision activities to the melting and refining process. No risk of human errors, for instance over¬oxidation with manual operated lances, is anymore present. One of these injection technologies, KT Injection System, a product of Techint Technologies, has performed a very big development during the last two years, with more than twenty projects started up worldwide. This paper is presented the study of the performances of KT Injection System. Comparisons between the situation before and after the installation, on all the major parameters of the EAF, give interesting information on injection efficiencies and furnace sustainable productivity increases.